Power for development : a review of the World Bank Group's experience with private participation in the electricity sector - Manibog, Fernando Reyes; Dominguez, Rafael; Wegner, Stephan (Washington, D.C. : World Bank, 2003)
This study is a joint review by the World Bank Group's three evaluation units. IT evaluates the performance of the world Bank Group during the 1990s in promoting private sector development in the electric power sector. its main message is that where countries showed a commitment to advancing reforms and wheepsde programs were properly implemented, psde has delivered its expected benefits.
Includes bibliographical references (p. 121-132).
Text in English; with summary in English, French, and Spanish.
opc13/03/15
Loans
Keywords: Electric utilities -- Privatization; Electric utilities -- Deregulation; Economic development projects -- Evaluation; World Bank Group